Development from below: Social accountability in natural resource management - Kishan Khoday; Leisa Perch (International Policy Centre for Inclusive Growth (IPC-IG), 2012)
[Introduction] We live in a time of transformational change, with society, economy, ecology and politics in a state of flux the world over. Of particular focus in this Working Paper are the implications for mineral-dependent economies of living in an increasingly resource-constrained world. Both countries for which growth depends on the extraction, refinement and export of such minerals, and those whose growth depends indirectly on the use of minerals in other resource-dependent industrial processes are considered. Attention is also placed on countries newly emerging as mineral-rich economies and for whom mineral exploitation will begin to play an increasing role in the structure and scale of growth. In the broader policy context, our focus is on the transition to a model of natural resource governance where goals of inclusion and sustainability are no longer secondary considerations but rather central ones. (...)
Keywords: 330; Entwicklung; Natürliche Ressourcen; Ressourcenökonomik; Nachhaltigkeitsbericht